2005
DOI: 10.1007/s11104-005-5997-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Phytotoxicity of Chromium in Flooded Soils using Embedded Selective Ion Exchange Resin Method

Abstract: Chromium present in the forms of Cr(VI) or Cr(III) in soils. Since the toxicity and mobility of Cr(VI) are higher than those of Cr(III), it would be important to estimate soil Cr(VI) accurately in order to assess the phytotoxicity of Cr. Soil redox potential can influence the distribution of Cr between Cr(VI) and Cr(III) forms, and thus an in situ method which is not affected by the soil redox condition is needed for determining Cr(VI) availability in paddy fields. In this study, the Cu-saturated selective ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Soil redox potential can influence the distribution of Cr between Cr(VI) and Cr(III) forms. Cr(VI) reduction occurred in the flooded soils, thus Cr(VI) can be transformed to low-solubility cationic forms via reduction Lee et al 2005. Therefore, Cr bioavailability was very much low in the paddy soil.…”
Section: Resultsmentioning
confidence: 99%
“…Soil redox potential can influence the distribution of Cr between Cr(VI) and Cr(III) forms. Cr(VI) reduction occurred in the flooded soils, thus Cr(VI) can be transformed to low-solubility cationic forms via reduction Lee et al 2005. Therefore, Cr bioavailability was very much low in the paddy soil.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained from these extraction methods, however, may not necessarily reflect the metal uptake by plants, because the chemical solutions could alter the soil conditions greatly. Therefore, we propose using Cu-saturated selective ion exchange resin (DOWEX M4159), a resin that has high affinity for Cr(VI), to serve as an infinite sink to assess the bioavailability of soil Cr(VI), especially since the resin extraction method for soil metals is less destructive than the chemical extraction method (Lee et al, 2005;Yu et al, 2004). Our experimental results demonstrated that there was a significant negative correlation between the resin-extractable Cr(VI) and the height of wheat seedling growth.…”
Section: Introductionmentioning
confidence: 99%
“…The greater amount of organic matter in the forest soil mitigated the toxicity effect, possibly by immobilizing the soluble Cr added to the soils [72]. Lee et al [73] evaluated the toxicity of Cr (as K 2 Cr 2 O 7 ) in terms of its effect on the growth of rice seedlings on paddy soils; the toxicity occurred at 300 mg Cr(VI) kg À1 for the soil with pH 3.8 (organic matter 2.5 %) and at 75 mg Cr(VI) kg À1 for the soils with pH 6.9 (organic matter 2.2 %) and 8.1 (organic matter 2.6 %), showing clear evidence of increased Cr uptake and hence toxicity with increasing soil pH. This is at least partly due to the decrease in Cr(VI) sorption caused by expected increasing competition between the oxyanions (HCrO 4 À and CrO 4 2À ) and OH À anions for the positive charged sites on soil colloids as the pH increases On the other hand, at low pH values the dominant Cr(VI) species, HCrO 4 À can be easily adsorbed at positively charged sites.…”
Section: Chromiummentioning
confidence: 99%
“…In acidic environments Cr(VI) generally reduces to Cr(III), which is strongly retained onto soil colloids due to the availability of additional positive charges generated by the protonation of (organic and inorganic) colloidal surfaces. This strong retention considerably decreases the plant uptake and hence phytotoxicity of Cr(III) under acidic soil conditions [73].…”
Section: Chromiummentioning
confidence: 99%